Nation et apprentissage de la masculinité. L’exemple des jeunes Français au xixe siècle - Anne-Marie Sohn (Mélanges de la Casa de Velázquez)
Historians have long noted the contradiction in France between the masculine construction of political space and feminine representations of the nation. Starting in 1979, in his wide-ranging work on the Marianne, Maurice Agulhon began to inquire into the relationship between gender and Republic, a question then being debated by specialists in the history of women. But the subject is by no means confined to the Marianne, for the ousting of women from the political stage during the French Revolution has also raised conflicting interpretations which require discussion. It is only by delving into the particular way in which male adolescents and youths internalise the models of citizen and soldier that one can comprehend the relationship between nation, citizenship and the construction of masculinity. Juvenile fascination with the military heroics of the citizen in arms thus goes hand-in-hand with the urge to learn the political rules and behave as citizens, even before reaching voting age.